Loop Quantum Black Hole Extensions Within the Improved Dynamics - Gambini, Rodolfo; Olmedo, Javier; Pullin, Jorge (Frontiers in Astronomy and Space Sciences, 2021)
We continue our investigation of an improved quantization scheme for spherically symmetric loop quantum gravity. We find that in the region where the black hole singularity appears in the classical theory, the quantum theory contains semi-classical states that approximate general relativity coupled to an effective anisotropic fluid. The singularity is eliminated and the space-time can be continued into a white hole space-time. This is similar to previously considered scenarios based on a loop quantum gravity quantization.